Components and Models of PAI Curriculum Development - Raden Muliana; Nafsia Marasabessy; Andi Fitriani Djollong; Sudirman; Wisriani (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
The curriculum as an educational design has a very strategic position in all aspects of educational activities. Given the importance of curriculum development in education, preparation should refer to a strong and strong foundation. The foundation of curriculum development is not only needed by curriculum (macro) or written curriculum which is often referred to as the ideal curriculum, but must also be understood and used as a basis for consideration by the curriculum implementer (micro), namely education supervisors and teachers and other parties related to the task of education management, as a material that will be used as an instrument in coaching the implementation of the curriculum in each type and the level of education. With this important position, curriculum development cannot be done carelessly, but must be based on various considerations, or foundations so that it can be used as a foothold in organizing the educational process, so as to facilitate the achievement of educational and learning goals more efficiently and effectively.